A Cys2/His2 Zinc Finger Protein Acts as a Repressor of the Green Revolution Gene SD1/OsGA20ox2 in Rice (Oryza sativa L.). (23rd September 2020) - Duan, Min; Ke, Xiao-Juan; Lan, Hong-Xia; Yuan, Xi; Huang, Peng; Xu, En-Shun; Gao, Xiu-Ying; Wang, Ru-Qin; Tang, Hai-Juan; Zhang, Hong-Sheng; Huang, Ji
Abstract: Gibberellins (GAs) play important roles in the regulation of plant growth and development. The green revolution gene SD1 encoding gibberellin 20-oxidase 2 (GA20ox2) has been widely used in modern rice breeding. However, the molecular mechanism of how SD1 / OsGA20ox2 expression is regulated remains unclear. Here, we report a Cys2/His2 zinc finger protein ZFP207 acting as a transcriptional repressor of OsGA20ox2 . ZFP207 was mainly accumulated in young tissues and more specifically in culm nodes. ZFP207 -overexpression ( ZFP207OE ) plants displayed semidwarfism phenotype and small grains by modulating cell length. RNA interference of ZFP207 caused increased plant height and grain length. The application of exogenous GA3 could rescue the semidwarf phenotype of ZFP207OE rice seedlings. Moreover, ZFP207 repressed the expression of OsGA20ox2 via binding to its promoter region. Taken together, ZFP207 acts as a transcriptional repressor of SD1 / OsGA20ox2 and it may play a critical role in plant growth and development in rice through the fine-tuning of GA biosynthesis .